PDX-1 mRNA expression in endoscopic ultrasound-guided fine needle cytoaspirate: Perspectives in the diagnosis of pancreatic cancer. Issue 2 (February 2015) - Marzioni, Marco; Germani, Ugo; Agostinelli, Laura; Bedogni, Giorgio; Saccomanno, Stefania; Marini, Francesco; Bellentani, Stefano; Barbera, Carmelo; De Minicis, Samuele; Rychlicki, Chiara; Santinelli, Alfredo; Ferretti, Maurizio; et al.
Abstract Background and aims Endoscopic ultrasound-guided fine needle aspiration is routinely used in the diagnostic work up of pancreatic cancer but has a low sensitivity. Studies showed that Pancreatic Duodenal Homeobox-1 (PDX-1) is expressed in pancreatic cancer, which is associated with a worse prognosis. We aimed to verify whether the assessment of PDX-1 in endoscopic ultrasound-guided fine needle aspiration samples may be helpful for the diagnosis of pancreatic cancer. Methods mRNA of 54 pancreatic cancer and 25 cystic lesions was extracted. PDX-1 expression was assessed by Real-Time PCR. Results In all but two patients with pancreatic cancer, PDX-1 was expressed and was found positive in 7 patients with pancreatic cancer in which cytology was negative. The positivity was associated with a probability of 0.98 (95% CI 0.90–1.00) of having cancer and the negativity with one of 0.08 (95% CI 0.01–0.27). The probability of cancer rose to 1.00 (95% CI 0.97–1.00) for patients positive to both PDX-1 and cytology and fell to 0.0 (95% CI 0.00–0.15) in patients negative for both. Conclusions PDX-1mRNA is detectable in samples of pancreatic cancer. Its quantification may be helpful to improve the diagnosis of pancreatic cancer.